Standarisasi Kepuasan Wisatawan Pengguna Jasa Taman Rusa Lamtanjong Aceh Besar dan beberapa Faktor yang Mempengaruhinya - Nasir, Nasir; Zakaria, Zakaria; Yuslinaini, Yuslinaini (Lembaga KITA, 2019)
This study aims to determine the extent of tourist satisfaction in using the services of the Great Aceh Lamtanjong Deer Park, analytical equipment used is multiple linear regression with reliability testing and validity tests, so far the results of the study indicate that all independent variables have a positive effect on consumer satisfaction, from the results of the regression coefficient the physical evidence factor becomes the biggest factor affecting tourist satisfaction in the Lamtanjong Aceh Besar Deer Park, then responsiveness is the lowest factor affecting consumer satisfaction.Â Keywords: satisfaction, tourists, service users